Alterations of the IKZF1-IKZF2 tandem in immune cells of schizophrenia patients regulate associated phenotypes - Iván Ballasch; Laura López-Molina; Marcos Galán-Ganga; Anna Sancho-Balsells; Irene Rodríguez-Navarro; Sara Borràs-Pernas; M. Angeles Rabadan; Wanqi Chen; Carlota Pastó-Pellicer; Francesca Flotta; Wang Maoyu; Joaquín Fernández-Irigoyen; et al. (Journal of Neuroinflammation)
Abstract Schizophrenia is a complex multifactorial disorder and increasing evidence suggests the involvement of immune dysregulations in its pathogenesis. We observed that IKZF1 and IKZF2, classic immune-related transcription factors (TFs), were both downregulated in patients’ peripheral blood mononuclear cells (PBMCs) but not in their brain. We generated a new mutant mouse model with a reduction in Ikzf1 and Ikzf2 to study the impact of those changes. Such mice developed deficits in the three dimensions (positive–negative-cognitive) of schizophrenia-like phenotypes associated with alterations in structural synaptic plasticity. We then studied the secretomes of cultured PBMCs obtained from patients and identified potentially secreted molecules, which depended on IKZF1 and IKZF2 mRNA levels, and that in turn have an impact on neural synchrony, structural synaptic plasticity and schizophrenia-like symptoms in in vivo and in vitro models. Our results point out that IKZF1-IKZF2-dependent immune signals negatively impact on essential neural circuits involved in schizophrenia.